Dessulfurização oxidativa em diesel utilizando catalisadores à base de vanádio ou manganês - Mello, Mariele Iara Soares de (2012)
The oxidative desulfurization process (ODS) of a commercial diesel fuel was performed under mild conditions in the presence of catalysts based on vanadium or manganese, supported on alumina, clays (commercial, natural and pillared) and zeolites (NaX, NaY, beta, mordenite and ZSM-5). The catalysts were synthesized by wet impregnation and characterized by X-ray diffraction, textural analysis by N2 adsorption and scanning electron microscopy. The dibenzothiophene (DBT) was used as sulfur compound in catalytic evaluation. The reactions were performed using acetonitrile as solvent and the hydrogen peroxide as oxidant at 55°C. The reaction products were analized by gas chromatography (GC-FID). In the studied conditions, the process was efficient due to the DBT was converted to its corresponding sulfone. Both DBT and corresponding sulfone were extracted by the solvent. Removals and oxidations up to 100% of sulfur compound were achieved. The catalysts supported on ZSM-5 zeolite showed are more effective for oxidation reaction of sulfur compound, presenting the best results. It was observed for oxidation reaction, that vanadium catalysts were more effective and manganese catalysts showed best results for removal of sulfur compounds